QUALITY MODELS IN THE REGULATORY FRAMEWORK FOR THE ACCREDITATION OF THE UNIVERSITIES OF PERU - Flores Konja, Adrian Alejandro (2012)
This article is the result of a brief exploratory investigation of the relationship between quality models proposed by the administrative doctrine and the national accreditation process of Peruvian universities. The Peruvian university, reflecting on the political, social, cultural and technological changes in our society, is also experiencing a process of change, for example, a major expansion in university departments, modalities and number of students. However, this expansion process, often unplanned, has created serious doubts and questions about whether the expansion is ensuring the quality of professional training, research and social outreach. It must also be consistent with the social demands of the market and national development. To meet this need, we have promoted a system of accreditation of the quality of university education through the creation of a National Assessment, Accreditation and Certification of Educational Quality (SINEACE), was prepared in 2003 by the General Law of Education, 28044. They want to know if the quality models proposed in the accreditation standards of the system are consistent with organization doctrinal trends.